Discoidin Domain Receptors: Potential Actors and Targets in Cancer - Rammal, Hassan; Saby, Charles; Magnien, Kevin; Van-Gulick, Laurence; Garnotel, Roselyne; Buache, Emilie; El Btaouri, Hassan; Jeannesson, Pierre; Morjani, Hamid (Frontiers in Pharmacology, 2016)
The extracellular matrix critically controls cancer cell behavior by inducing several signaling pathways through cell membrane receptors. Besides conferring structural properties to tissues around the tumor, the extracellular matrix is able to regulate cell proliferation, survival, migration and invasion. Among these receptors, the integrins family constitutes a major class of receptors that mediate cell interactions with extracellular matrix components. Twenty years ago, a new class of extracellular matrix receptors has been discovered. These tyrosine kinase receptors are the two discoidin domain receptors DDR1 and DDR2. DDR1 was first identified in the Dictyostelium discoideum and was shown to mediate cell aggregation. DDR2 shares highly conserved sequences with DDR1. Both receptors are activated upon binding to collagen, one of the most abundant proteins in extracellular matrix. While DDR2 can only be activated by fibrillar collagen, particularly types I and III, DDR1 is mostly activated by type I and IV collagens. In contrast with classical growth factor tyrosine kinase receptors which display a rapid and transient activation, DDR1 and DDR2 are unique in that they exhibit delayed and sustained receptor phosphorylation upon binding to collagen. Recent studies have reported differential expression and mutations of DDR1 and DDR2 in several cancer types and indicate clearly that these receptors have to be taken into account as new players in the different aspects of tumor progression, from non-malignant to highly malignant and invasive stages. This review will discuss the current knowledge on the role DDR1 and DDR2 in malignant transformation, cell proliferation, epithelial to mesenchymal transition, migratory and invasive processes, and finally the modulation of the response to chemotherapy. These new insights suggest that DDR1 and DDR2 are new potential targets in cancer therapy.